2022
DOI: 10.24093/awej/vol13no1.25
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Learning Strategies in ESP Context: Knowledge and Implication

Abstract: The present study aims to explore the knowledge level and preferences regarding vocabulary learning strategies (VLSs) among the EFL university students studying English for Specific Purposes (ESP) courses. It also investigates the impact of vocabulary learning strategies on EFL learners’ performance. A sample of twenty students from an intact class participated in the study. For data collection, a triangulated approach has been employed through the usage of a questionnaire, semi-structured interviews, together… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the particular case of learners who attend English for Specific Purposes (ESP) courses, the sphere of vocabulary is essential. As various studies (Xhaferi 2010;Le Huong and Huy 2021;Al Zahrani and Chaudhary 2022) have explained, teaching specialized vocabulary involves several difficulties, but it is crucial for ESP learners:…”
Section: Discussionmentioning
confidence: 99%
“…In the particular case of learners who attend English for Specific Purposes (ESP) courses, the sphere of vocabulary is essential. As various studies (Xhaferi 2010;Le Huong and Huy 2021;Al Zahrani and Chaudhary 2022) have explained, teaching specialized vocabulary involves several difficulties, but it is crucial for ESP learners:…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed a significant positive correlation between using VLS and vocabulary knowledge ( Alahmadi et al, 2018 ; Alahmadi and Foltz, 2020 ; Al-Zahrani and Chaudhary, 2022 ). Al-Zahrani and Chaudhary (2022) confirmed that implementing various VLSs significantly influenced the performance of the English language learners in English for Specific Purposes classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies have revealed a significant positive correlation between using VLS and vocabulary knowledge ( Alahmadi et al, 2018 ; Alahmadi and Foltz, 2020 ; Al-Zahrani and Chaudhary, 2022 ). Al-Zahrani and Chaudhary (2022) confirmed that implementing various VLSs significantly influenced the performance of the English language learners in English for Specific Purposes classroom. The findings have important pedagogical implications for teachers within the ESP context since they inform about students' knowledge levels and preferences for VLSs, and assist in using efficient teaching strategies that can lead to good achievement of vocabulary knowledge.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation